2008
DOI: 10.1007/s10653-008-9198-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and sources of PAHs in an urban river system in Beijing, China

Abstract: Water samples from 20 locations on rivers in the Tongzhou District of Beijing were collected four times from July 2005 to March 2006. In addition, sediment samples were collected in July 2005. All samples were analyzed for 16 US Environmental Protection Agency (EPA) priority pollutants polycyclic aromatic hydrocarbons (PAHs). The concentration, distribution, seasonal variation, and sources of the 16 PAH compounds identified in the water samples, suspended particles, and surface sediments were then evaluated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 28 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…High PAH levels have been previously reported for streams in Tianjin (Shi et al 2005;Qi et al 2011). The occurrence and characterization of PAHs have also been reported in urban river systems in Beijing (Zhang et al 2004;Shen et al 2009). Fuel and biomass combustion, coke ovens, etc., are clearly the primary sources of PAHs in the rivers in the Beijing and Tianjin area (Shi et al 2007(Shi et al , 2009).…”
Section: Introductionmentioning
confidence: 77%
“…High PAH levels have been previously reported for streams in Tianjin (Shi et al 2005;Qi et al 2011). The occurrence and characterization of PAHs have also been reported in urban river systems in Beijing (Zhang et al 2004;Shen et al 2009). Fuel and biomass combustion, coke ovens, etc., are clearly the primary sources of PAHs in the rivers in the Beijing and Tianjin area (Shi et al 2007(Shi et al , 2009).…”
Section: Introductionmentioning
confidence: 77%
“…2), whereas the three-ring and four-ring PAH portions were considerably higher in water from big city CQ and CS than from town or counties in Hubei area. Studies (Hong et al 2012;Shen et al 2009;McCready et al 2000;Boonyatumanond et al 2006) found that the composition of 16 priority PAHs in sediments was at similar percentages for five-and six-ring compounds in both agricultural and urban section in rivers, while the four-ring PAHs were considerably higher in surface sediments in urban section. Hong et al (2012) concluded that PAHs in sediment record urbanization effects on environmental changes.…”
Section: Spatial Pattern and Composition Of Pah In Tgrmentioning
confidence: 99%
“…If PAHs are higher than standard level in our living environment, they may have potential hazard of carcinogenicity, mutagenicity, immunotoxicity and genotoxicity on human body (Shen et al 2009;Pathiratne et al 2007;Yan et al 2009). Some PAHs were produced from the accidental spillage of crude and refined oil and generated through incomplete combustion of wood, coal and fossil fuels et al (Zhang et al 1993;Harrison et al 1996).…”
Section: Introductionmentioning
confidence: 99%